Vulnerability of Individuals With Mental Disorders to Epistemic Injustice in Both Clinical and Social Domains. Issue 4 (19th May 2018) - Kurs, Rena; Grinshpoon, Alexander
Abstract : Many individuals who have mental disorders often report negative experiences of a distinctively epistemic sort, such as not being listened to, not being taken seriously, or not being considered credible because of their psychiatric conditions. In an attempt to articulate and interpret these reports we present Fricker's concepts of epistemic injustice (Fricker, 2007, p. 1) and then focus on testimonial injustice and hermeneutic injustice as it applies to individuals with mental disorders. The clinical impact of these concepts on quality of care is discussed. Within the clinical domain, we contrast epistemic injustice with epistemic privilege and authority. We then argue that testimonial and hermeneutic injustices also affect individuals with mental disorders not only when communicating with their caregivers but also in the social context as they attempt to reintegrate into the general society and assume responsibilities as productive citizens. Following the trend of the movement of mental health care to the community, the testimonies of people with mental disorders should not be restricted to issues involving their own personal mental states.